Between “Public” Islam and “Private” Sufism: Producing a National Icon through Mass Mediated Hagiography - Aishima, Hatsuki (Die Welt des Islams, 2016)
To what extent can a national hero be a Sufi? This article examines the much contested yet still underexplored relationship between the public discourse of modernity and Sufism by looking at how television producers dealt with Sufi elements in ʿAbd al-Ḥalīm Maḥmūd’s (1910–78) biography. The Egyptian public remembers ʿAbd al-Ḥalīm Maḥmūd as a Shaykh al-Azhar and a distinguished scholar of Sufism of the 1970s. His biopic series broadcast on national television during the Ramadan of 2008 showed the delicate nature of exposing Sufi practices in public Islam. ʿAbd al-Ḥalīm’s career path leading up to the level of a high-ranking scholar of al-Azhar was celebrated as the result of strong faith in God. However, his Sufi practices were modified to correspond to the television producers’ understanding of correct Sufism and to show how “private” spiritual pursuits would not hinder one from being an economically productive individual in the public sphere.